Proposed Social Media Marketing Strategy For Improving Sales In Food And Beverage Business Sector - Rahmandi*, Dwinan; Aprianingsih, Atik (Universitas Syiah Kuala, 2023)
Pietro Coffee was founded on May 1st, 2019 at Trunojoyo Street No 11, Bandung. Pietro takes its name from the icon of a flying squirrel (sugar glider) with the Latin name